Arrangement Of Vehicle and Passenger Space Circulation Based on Wayfinding Approach at Ciakar Sumedang Bus Terminal - Reva Nuary Dwitayana (Universitas Siliwangi, 2023)
Crossings between elements of vehicle and passenger spaces are the main problem of the obstruction of circulation within the bus terminal area, therefore bus terminals as public service facilities need to pay attention to movement patterns that are dynamic and flexible for smooth circulation for humans and public transportation. The physical assets of the bus terminal building are important transportation infrastructure in each region, but the Ciakar Bus Terminal has not met the criteria and has not implemented the wayfinding approach and type A rule standards. implementation of the project design. The theoretical basis used is spatial planning of the physical assets of the bus terminal supported by the wayfinding approach. This project uses the blueprint method with primary and secondary data sources. Data collection techniques using observation, interviews, and documentation studies. Project results include; (1) the design of each vehicle and passenger space indicator based on the wayfinding approach; (2) the estimated cost of structuring and developing assets in this project is Rp. 13,417,742,963. This project can be realized by reviewing the budget plan and conducting a review of asset utilization.